Innovations, challenges, and minimal information for standardization of humanized mice. Issue 7 (24th June 2020) - Stripecke, Renata; Münz, Christian; Schuringa, Jan Jacob; Bissig, Karl‐Dimiter; Soper, Brian; Meeham, Terrence; Yao, Li‐Chin; Di Santo, James P; Brehm, Michael; Rodriguez, Estefania; Wege, Anja Kathrin; Bonnet, Dominique; et al.
Abstract: Mice xenotransplanted with human cells and/or expressing human gene products (also known as "humanized mice") recapitulate the human evolutionary specialization and diversity of genotypic and phenotypic traits. These models can provide a relevant in vivo context for understanding of human‐specific physiology and pathologies. Humanized mice have advanced toward mainstream preclinical models and are now at the forefront of biomedical research. Here, we considered innovations and challenges regarding the reconstitution of human immunity and human tissues, modeling of human infections and cancer, and the use of humanized mice for testing drugs or regenerative therapy products. As the number of publications exploring different facets of humanized mouse models has steadily increased in past years, it is becoming evident that standardized reporting is needed in the field. Therefore, an international community‐driven resource called "Minimal Information for Standardization of Humanized Mice" (MISHUM) has been created for the purpose of enhancing rigor and reproducibility of studies in the field. Within MISHUM, we propose comprehensive guidelines for reporting critical information generated using humanized mice. Abstract : Humanized mice are at the forefront of biomedical research and becoming more mainstream preclinical models. This comprehensive review talks about innovations and challenges regarding the reconstitution of human immunity and introduces "Minimal Information for Standardization of Humanized Mice" (MISHUM).